PERCEPTIONS OF THE ACADEMIC SOCIETY ON COMMUNICATION STYLE AND ETHICS IN THE 2024 ELECTION PRESIDENTIA DEBATES - Danang Try Purnomo; El Guyanie, Gugun; Arifin, Ferdi; Husin Al Fatah, Muhammad (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2025)
Abstract The presidential candidate debate in the 2024 election is an interesting concern for the academic community. This is related to the focus of this research, which is to see the perceptions of the academic community towards the style and ethics of debate communication affecting choice preferences. This type of research is descriptive qualitative and data collection is done using survey and interview techniques. The results obtained in this study illustrate the perception that the aggressive-assertive communication style dominates in debate shows, while in communication ethics the elements of honesty-objectivity, respect, and empathy are obtained in the process of the debate. Overall, both communication styles and ethics are still within the limits of relatively reasonable and positive communication. From the aspect of the relevance of the style and ethics of debate communication to the choice of presidential and vice presidential candidates, it shows a significant influence, namely the broadcast of the debate has increased voters' confidence in making their political choices.